HYDROXYL DRIVEN RECONSTRUCTION OF THE POLAR NIO(111) SURFACE - Libuda, Jörg; et al. (Surface Science, 1994)
We have studied the reconstruction of the polar NiO(111) surface predicted recently by D. Wolf with low energy electron diffraction. Thin NiO films (10-20 angstrom) are used as substrates. As prepared, the films with a p(1 x 1) NiO(111) structure are covered with hydroxyl groups, which may be removed through a simple heat treatment. As the hydroxyl groups are desorbed, the surface reconstructs, exhibiting a diffuse p(2 x 2) structure. Readsorption of water onto the reconstructed surface lifts the reconstruction and again leads to the formation of the p(1 x 1) hydroxyl covered surface.